2019
DOI: 10.1161/jaha.118.010974
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mitral Regurgitation Severity and Cause on Effort Tolerance–Integrated Stress Myocardial Perfusion Imaging and Echocardiographic Assessment of Patients With Known or Suspected Coronary Artery Disease Undergoing Exercise Treadmill Testing

Abstract: Background Mitral regurgitation ( MR ) has the potential to impede exercise capacity; it is uncertain whether this is because of regurgitation itself or the underlying cause of valvular insufficiency. Methods and Results The population comprised 3267 patients who underwent exercise treadmill myocardial perfusion imaging and transthoracic echocardiography within 6±8 days. MR was present in 28%, including 176 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…13,14 Left-side parameters and exercise tolerance Left atrial volume index was the only left-side parameters associated with CPET (peak VO 2 in the overall population). The absence of relationship with LVEF has been previously described, 4 but recent reports have suggested the important role of LV diastolic dysfunction 35 and/or MR 36 on exercise capacity. While an association between MR and peak VO 2 was present in our univariate model, MR haemodynamic repercussion and subsequent RV dysfunction and/or PH were stronger predictors of CPET in our cohort.…”
Section: Impact Of Tricuspid Regurgitation On Exercise Tolerancementioning
confidence: 88%
“…13,14 Left-side parameters and exercise tolerance Left atrial volume index was the only left-side parameters associated with CPET (peak VO 2 in the overall population). The absence of relationship with LVEF has been previously described, 4 but recent reports have suggested the important role of LV diastolic dysfunction 35 and/or MR 36 on exercise capacity. While an association between MR and peak VO 2 was present in our univariate model, MR haemodynamic repercussion and subsequent RV dysfunction and/or PH were stronger predictors of CPET in our cohort.…”
Section: Impact Of Tricuspid Regurgitation On Exercise Tolerancementioning
confidence: 88%
“…Moreover, MVP symptoms are frequently disproportionate to objective findings through exhaustive clinical and laboratory investigation. Although several studies have observed that advanced MR impairs exercise tolerance independent of left ventricular ischemia and dysfunction [21,22], little is known regarding the influence of trivial or mild MR on exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these studies suggest that pMVR treatment is associated with an improvement in symptoms, quality of life, functional status and, in some but not all studies, exercise capacity. 8 , 9 , 10 , 11 , 12 Indeed, although MR directly impairs exercise performance, 13 both the COAPT and the MITRA‐FR trials reported a null effect of pMVR on the 6‐min walk test (6MWT). 6 , 7 , 14 Differently, several other studies suggested an improved exercise performance, 11 , 15 assessed in the great majority of reports by 6MWT.…”
Section: Introductionmentioning
confidence: 99%